PENGARUH ORGANIZATIONAL COMMITMENT DAN JOB INSECURITY TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Pada Guru SMK Pariwisata Triatma Jaya Badung) - Kumala Sari, Anak Agung Pertiwi; Riana, I Gede; Piartrini, Putu Saroyini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p04, 2017)
The organization’s goals will be achieved if supported by human resources who have high commitment of organizational commitment and organizational citizenship behavior (OCB). The research is aimed to know the influence of organizational commitment and job insecurity on organizational citizenship behavior (Studies on Tourism Vocational High School teachers Triatma Jaya Badung. Population in this research are 39 responden that work as teachers at Tourism Vocational High School Triatma Jaya Badung. Primary data was taken from respondent. Multiple Regression Analysis methode was used for hypothesis analysis as well with SPSS version 13.0 was used as software application. The result showed that (1) Organizational commitment gave significant positive effect toward organizational citizenship behavior (2) job insecurity gave significant negative effect toward organizational citizenship behavior. Suggested for further research in other to boarden the scope of research into multiple location such as Tabanan, Singaraja and Semarang and separating respondents into each position group, and examines the influence of organizational commitment and job insecurity on organizational citizenship behavior in Tourism Vocational High School teachers Triatma Jaya.
Keywords: Organizational Commitment, Job Insecurity, Organizational Citizenship Behavior